Particle Analysis – A Combined Method to Analyze the Colloidal Characteristics of Particles - Titze, Jean; Christian, Manuel; Ilberg, Vladimír; Jacob, Fritz (BrewingScience, 2010)
Particle analysis and its potential in describing the physico-chemical characteristics of particles in beer were investigated. It was the aim to figure out the feasibility for its application in brewing and beverage science. To describe existing problems in the beverage industry caused by insufficient physico-chemical stability of the beverages a rule of great generality according to the particle characteristics was also defined as follows: Beverages are liquids, in which colloids, also called particles, exist in disperged (e.g. beer) or emulsified (e.g. milk) form. One main particle characteristic is the surface. This can be seen in many interfacial phenomena, like the surface potential. Mathematically it was shown, that especially for small particles the ratio between surface and volume increases. Surfaces carry electric charges, which terminate or change the physico-chemical characteristics of the particles. By combining (1) the particle charge detection with polyelectrolyte titration for determining the surface charge, the surface potential and charge density of particles with (2) the particle size analysis by dynamic stray light to analyze the particle size and particle size distribution, the particles could be characterized.